Pareto optimality for nonlinear infinite dimensional control systems - Evgenios P. Avgerinos; Nikolaos S. Papageorgiou (International Journal of Mathematics and Mathematical Sciences)
In this note we establish the existence of Pareto optimal solutions for nonlinear, infinite dimensional control systems with state dependent control constraints and an integral criterion taking values in a separable, reflexive Banach lattice. An example is also presented in detail. Our result extends earlier ones obtained by Cesari and Suryanarayana.